(3YgOI GdeDed hYOI GdeJeKds - (3YHO GdQMef Hf YHO Gddg Hf Ydj GdfLej, GdbQjGfj GdCfOdSjs ((3ecI s)
(3ChdgG (B:s
(3Cgd GdCfOdS hdbjJg ef aVdGA Cgd GdTGe aUGQ cJGHkG ef LRAjf ebQHjf SejJg HYgOI GdeDed hYOI GdeJeKd s
(3BNQgG (B:s
(3bdJ(B: (3hCfTOfjgG HOeTb SfI SJ hCQHYjf hSJ eFI TjoNfG YgOI GdeDed HNW eQJHg s
(3HgG fXGe GdJYbjHIs
(3aj GdeMGVQGJ (B- (3LRAGf aj eLdO hGMOs
(3cJHgG GHf GdeDda haQZ efgG aj MjGI CHjgs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs